Povidone iodine treatment is deleterious to human ocular surface conjunctival cells in culture. Issue 1 (16th September 2020) - Swift, William; Bair, Jeffrey A; Chen, Wanxue; Li, Michael; Lie, Sole; Li, Dayu; Yang, Menglu; Shatos, Marie A; Hodges, Robin R; Kolko, Miriam; Utheim, Tor P; Scott, Wendell; et al.
Abstract : Objective: To determine the effect of povidone iodine (PI), an antiseptic commonly used prior to ocular surgery, on viability of mixed populations of conjunctival stratified squamous and goblet cells, purified conjunctival goblet cells and purified conjunctival stromal fibroblasts in primary culture. Methods and analysis: Mixed population of epithelial cells (stratified squamous and goblet cells), goblet cells and fibroblasts were grown in culture from pieces of human conjunctiva using either supplemented DMEM/F12 or RPMI. Cell type was evaluated by immunofluorescence microscopy. Cells were treated for 5 min with phosphate-buffered saline (PBS); 0.25%, 2.5%, 5% or 10% PI in PBS; or a positive control of 30% H2 O2 . Cell viability was determined using Alamar Blue fluorescence and a live/dead kit using calcein/AM and ethidium homodimer-1 (EH-1). Results: Mixed populations of epithelial cells, goblet cells and fibroblasts were characterised by immunofluorescence microscopy. As determined with Alamar Blue fluorescence, all concentrations of PI significantly decreased the number of cells from all three preparation types compared with PBS. As determined by calcein/EH-1 viability test, mixed populations of cells and fibroblasts were less sensitive to PI treatment than goblet cells. All concentrations of PI, except for 0.25% used with goblet cells, substantially increased the number of dead cells for all cell populations. The H2 O2 control also significantly decreased the number and viability of all three types of cells in both tests. Conclusion: We conclude that PI, which is commonly used prior to ocular surgeries, is detrimental to human conjunctival stratified squamous cells, goblet cells and fibroblasts in culture.